THE INFLUENCE OF WORDWALL MEDIA ON THE LEARNING OUTCOMES OF GRADE III STUDENTS IN SCIENCE LEARNING CHANGES IN THE FORM OF OBJECTS - Aini Soraya Tosari; kasriman (Universitas Majalengka, 2024)
Examining the impact of Wordwall Media on the Academic Performance of Third Grade Science Students at SDN Tanah Baru 1 in the 2023–2024 School Year is the primary objective of this research. The study employed a quantitative approach and a quasi-experimental design for its methodology. Classes III A and B will serve as the experimental and control groups, respectively, in this sampling strategy. Using point biserian correlation, we tested the validity of up to 30 multiple-choice questions; 20 of them passed, while 10 did not. The scientific learning outcomes instrument was deemed